Cost in high impact journals: The problem for researchers from low and middle income countries - Gupta, Arti; Reddy B, Venkatashiva; Kumar Solanki, Hariom (Public Health Review: International Journal of Public Health Research, 2018)
Introduction: Research publication is an important means of career progression for young professionals. At many universities, it is a mandatory requirement to publish a certain number of research paper for raise, promotion, or even recruitment. Today wider acceptance of the open access model has increasingly shifted the cost of publication from the reader to the researcher. The present study aims to study the processing and publication, pricing of index journals. Method: This was anobservational study, studying journals indexed in one of the freely indexing services. We retrieved list of all journals indexed in PubMed between June and December 2015 from the website. We non randomly selected 150 of these for further evaluation study. The outcome measure was publication cost, and pre-processing cost. We retrieved cost related to publication and publication site of the journal from the official website of these selected journals. For cost estimation, a typical article length of 15 pages was assumed. We excluded journals whose websites did not provide information regarding such cost or were in any language other than English. Results: Out of 5623 indexed journals in PubMed as of July 2015, 150 journals were included in the study. A total of 33 journals was excluded, remaining 117 journals formed the final sample size of this study. Nearly 80% of the journals had publication cost. The median cost of publication of a typical paper was 2590 US. More than three quarter of the journals were published from the developed world like United States of America, United Kingdom and European region. Conclusion: Though the cost of publication was not uniformly high, the average cost was relatively high for researchers in low and middle-incomecountries.It could be as much as one-month’s salary of these professionals. This could be a hindrance for publishing research and in the career advancement of these researchers